Pengaruh Perjalanan Penduduk Perumahan Puri Yuhana Dan Bukit Khatulistiwa Terhadap Rantai Perjalanan. - Jexon Takaeb; Rais Rachman; Monika Datu Mirring Palinggi (Paulus Civil Engineering Journal, 2021)
In making a work trip, apart from being faced with the time of departure and the mode used, the journey of the residents of the Puri Yuhana and Bukit Khatulistiwa housing estates on their work trips is not only direct to the right destination but there are several workers who take school children or other families first and then go to the right place. work or take care of office work elsewhere then go to work. This study aims to (1) Identify the Characteristics of Residents of Puri Yuhana Housing and Bukit Khatulistiwa. (2) Knowing the Effect of Traveling Residents of Puri Yuhana Housing and Bukit Khatulistiwa on the Travel Chain. This research was conducted in Puri Yuhana Housing and Bukit Khatulistiwa, Jalan Perintis Kemerdekaan km 4, Biringkanaya sub-district, Makassar. The results showed that the pattern of the travel chain for the residents of the Puri Yuhana Housing was dominant with the pattern of home – taking children to school – workplace – home, significantly influenced by the number of family members who worked and when they came home from work, while the pattern of the travel chain for the residents of Bukit Khatulistiwa Housing was dominant. with the homework – home pattern, significantly influenced by the number of family members, motorcycle ownership, departure time, and travel time